Characterization of the Widmanstätten structure in γ-TiAl alloy using an EBSD-FIB-TEM combined process. (1st January 2023) - Gao, Zitong; Hu, Rui; Gao, Xiangyu; Wu, Yulun; Zou, Hang; Li, Jinguang; Zhou, Mi
Abstract: The crystallography and interface atomic structure of Widmanstätten structure in γ-TiAl alloy were characterized using a well-designed EBSD-FIB-TEM combined preparation-characterization process. This method realizes the preparation of the TEM samples with a specific zone axis by bringing the EBSD and FIB techniques together, and is not only site-specific but also crystallographic-orientation-specific. By using this method, the atomic structure of the special Σ11 CSL interface between Widmanstätten and lamellar structures was characterized successfully. The Σ11 interface was perfectly coherent on the atomic scale and straight on the micron scale along the low-energy {113}γ faces, providing strong evidence of the sympathetic nucleation mechanism of the Widmanstätten structure, which was further discussed. Moreover, the EBSD-FIB-TEM method is expected to be efficient in the preparation-characterization of unevenly distributed microstructures and interfaces with specific orientation relationships, and to further expand the capability of the FIB technique. Graphical abstract: Image, graphical abstract